2012
DOI: 10.1021/ic201841m
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Divalent Germanium Alkoxide Complexes Is in Sharp Contrast to the Heavier Tin and Lead Analogues

Abstract: The chemistry of β-diketiminate germanium alkoxide complexes has been examined and shown to be in sharp contrast to its heavier congeners. For instance, (BDI)GeOR (BDI = [{N(2,6-(i)Pr(2)C(6)H(3))C(Me)}(2)CH], R = (i)Pr, (s)Bu, (t)Bu) does not react with carbon dioxide to form a metal carbonate complex. Addition of aliphatic electrophiles, such as methyl iodide or methyl triflate, results in the net oxidative addition to the germanium, giving cationic tetravalent germanium complexes, [(BDI)Ge(Me)OR][X] (X = I, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 37 publications
3
28
2
Order By: Relevance
“…In 5 , the Ge(1)–O(1) and Ge(1)–O(3) bond lengths (Table ) of 2.226(19) and 2.2509(18) Å, respectively, are understandably much longer than previously reported Ge–alkoxide bonds because of their purely coordinative characteristics. The respective Ge(1)–O(2) and Ge(1)–O(4) bond lengths of 1.8931(18) and 1.9086(18) Å are much closer to the reported Ge–O bond lengths in [(L)GeOC(H) 2 (PhOMe‐4)] {L = N(C 6 H 2 [C(H)Ph 2 ] 2 i Pr‐2,6,4)(Si i Pr 3 ), 1.8120(19) Å}, [(BDI)GeO t Bu] {BDI = [N(2,6‐ i Pr 2 C 6 H 3 )C(Me)] 2 CH, 1.8284(3) Å}, and [LGe(O i Pr)(HO i Pr)] [L = amine(triphenolate), 1.799(2) Å] . Similarly, in 10 , the respective Sn(1)–O(1) and Sn(1)–O(3) bond lengths of 2.397(2) and 2.366(2) Å are longer than those of common Sn–alkoxide bonds, whereas the Sn(1)–O(2) [2.110(2) Å] and Sn(1)–O(4) bond lengths [2.099(2) Å] showed similar characteristics to those of previously reported complexes such as (BDI)SnO i Pr, (BDI)SnO t Bu, and [Sn(C 5 H 7 O 2 )(C 2 H 3 O 2 )], which have Sn–O bond lengths of 2.000(5), 2.0179(16), and 2.156(4) Å, respectively.…”
Section: Resultssupporting
confidence: 68%
“…In 5 , the Ge(1)–O(1) and Ge(1)–O(3) bond lengths (Table ) of 2.226(19) and 2.2509(18) Å, respectively, are understandably much longer than previously reported Ge–alkoxide bonds because of their purely coordinative characteristics. The respective Ge(1)–O(2) and Ge(1)–O(4) bond lengths of 1.8931(18) and 1.9086(18) Å are much closer to the reported Ge–O bond lengths in [(L)GeOC(H) 2 (PhOMe‐4)] {L = N(C 6 H 2 [C(H)Ph 2 ] 2 i Pr‐2,6,4)(Si i Pr 3 ), 1.8120(19) Å}, [(BDI)GeO t Bu] {BDI = [N(2,6‐ i Pr 2 C 6 H 3 )C(Me)] 2 CH, 1.8284(3) Å}, and [LGe(O i Pr)(HO i Pr)] [L = amine(triphenolate), 1.799(2) Å] . Similarly, in 10 , the respective Sn(1)–O(1) and Sn(1)–O(3) bond lengths of 2.397(2) and 2.366(2) Å are longer than those of common Sn–alkoxide bonds, whereas the Sn(1)–O(2) [2.110(2) Å] and Sn(1)–O(4) bond lengths [2.099(2) Å] showed similar characteristics to those of previously reported complexes such as (BDI)SnO i Pr, (BDI)SnO t Bu, and [Sn(C 5 H 7 O 2 )(C 2 H 3 O 2 )], which have Sn–O bond lengths of 2.000(5), 2.0179(16), and 2.156(4) Å, respectively.…”
Section: Resultssupporting
confidence: 68%
“…The average GeN bond lengths in these compounds 3 (1.979 Å), 4 (1.961 Å), 5 (1.971 Å), and 6 (1.986 Å) are almost identical to the corresponding bond lengths in germylene monocyanide complex 2 (average: 1.972 Å). The GeO bonds in these compounds ( 3 (1.872(1) Å), 4 (1.946(4) Å), 5 (1.907 Å; average), and 6 (1.875(4) Å)) are longer than the GeO bond (1.8284(3) Å) in Fulton’s germylene alkoxide complex [GeO t Bu(L 2 )] 15c…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, the groundbreaking achievements have been accomplished by Power et al, who demonstrated that the sterically encumbered germylenes (Ar′) 2 Ge (Ar′ = 2,6‐Ar 2 –C 6 H 3 ; Ar = 2,4,6‐Me 3 –C 6 H 2 or 2,6‐ i Pr‐C 6 H 3 ) activate H 2 and NH 3 ,, and additional examples illustrating their intriguing reactivity followed . A high propensity to react with unsaturated substrates such as alkynes,, alkenes, dienes, carbonyl compounds,, isocyanides represents another typical property of germylenes. As a contribution to this field, we have recently reported the synthesis of an N , N ‐chelated germylene, [( i Pr) 2 NB(N‐2,6‐Me 2 C 6 H 3 ) 2 ]Ge ( 1 ), that exerts the typical, germylene‐like, reactivity toward dienes and alkynes .…”
Section: Introductionmentioning
confidence: 99%